2012
DOI: 10.1007/s11060-012-0861-0
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab therapy for adults with recurrent/progressive meningioma: a retrospective series

Abstract: Intracranial meningiomas are often indolent tumors which typically grow over years to decades. Nonetheless, meningiomas that progress after maximum safe resection and radiation therapy pose a significant therapeutic challenge and effective therapies have yet to be identified. Preclinical studies implicate angiogenesis in the pathophysiology of more aggressive meningiomas, suggesting that anti-angiogenic therapies may be of utility in this setting. We performed a retrospective review of fourteen patients with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(116 citation statements)
references
References 40 publications
4
101
0
3
Order By: Relevance
“…VEGF inhibitors such as bevacizumab have been shown to reduce baseline peritumoral edema as well as edema following radiosurgery and radiation therapy. 14,15 We have also reported on the use of bevacizumab for arteriovenous malformations and have used it rarely in the setting of other benign intracranial pathologies. 28 While bevacizumab was part of the current study, there is substantial reason to believe that it would be of therapeutic value for meningioma patients with worsening edema and particularly those who are intolerant of, or whose edema is refrac- tory to, corticosteroid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF inhibitors such as bevacizumab have been shown to reduce baseline peritumoral edema as well as edema following radiosurgery and radiation therapy. 14,15 We have also reported on the use of bevacizumab for arteriovenous malformations and have used it rarely in the setting of other benign intracranial pathologies. 28 While bevacizumab was part of the current study, there is substantial reason to believe that it would be of therapeutic value for meningioma patients with worsening edema and particularly those who are intolerant of, or whose edema is refrac- tory to, corticosteroid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…48,61 Bevacizumab (Avastin), a humanized monoclonal antibody direct VEGF inhibitor, has been investigated as a possible therapeutic agent that could halt or reverse tumor-related angiogenesis. Several small-scale retrospective studies have been published, with mixed results, 42,49,55 and there is a need for larger Phase II trials. The VEGF has also been shown to crossactivate other growth factor pathways, 59 an observation that seems to be a recurring theme with new advances in understanding of cell signaling in meningiomas.…”
Section: Angiogenesis Inhibitionmentioning
confidence: 99%
“…38,64,73,76,83 One trial with 48 patients having intracranial meningioma who were followed up for a median period of 18 months showed that 29% of these patients had at least a 20% reduction in meningioma volume; 76 however, this reduction was not sustained over time, and a molecular analysis yielded no correlation of VEGF pathway expression with treatment responses. Identifying the critical gene targets in spinal meningioma will improve the design of clinical treatments.…”
Section: Meningiomasmentioning
confidence: 99%